2005
DOI: 10.1111/j.1365-2141.2005.05432.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sickle cell lung disease: new insights into the diagnosis, pathogenesis and treatment of pulmonary hypertension

Abstract: SummaryPulmonary hypertension is a common complication of sickle cell disease (SCD). In spite of the mild elevations in pulmonary artery pressures in these patients, the associated morbidity and mortality is high. In fact, in adult patients with SCD, pulmonary hypertension is emerging as the major independent risk factor for death. The aetiology of pulmonary hypertension is probably multifactorial, including haemolysis, impaired nitric oxide bioavailability, chronic hypoxaemia, thromboembolism, parenchymal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 137 publications
(170 reference statements)
1
57
1
20
Order By: Relevance
“…Taken together, SC pulmonary hypertension may be due to more prominent relative contributions by other mechanisms for remodeling the pulmonary vasculature including activation of the endothelin 1 and prostocyclin/thromboxane A 2 pathways [37]. In contrast, the contributions of these two pathways in the severe hemolytic anemias like homozygous SCD and b thalassemia major occur in addition to alterations in the NO signaling pathway [38][39][40]. Moreover, these observations justify further study of SCD compound heterozygotes and their less intense hemolytic anemia as a more sensitive population for elucidating non-hemolytic mechanisms that may also contribute to the development of secondary pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, SC pulmonary hypertension may be due to more prominent relative contributions by other mechanisms for remodeling the pulmonary vasculature including activation of the endothelin 1 and prostocyclin/thromboxane A 2 pathways [37]. In contrast, the contributions of these two pathways in the severe hemolytic anemias like homozygous SCD and b thalassemia major occur in addition to alterations in the NO signaling pathway [38][39][40]. Moreover, these observations justify further study of SCD compound heterozygotes and their less intense hemolytic anemia as a more sensitive population for elucidating non-hemolytic mechanisms that may also contribute to the development of secondary pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In particular both the absence of prominent laboratory features of hemolysis and the poor survival for patients with high TRV's should prompt clinicians to perform a comprehensive evaluation to rule out other etiologies of pulmonary hypertension in Hb SC (e.g. acute pulmonary embolism, chronic thromboembolic pulmonary hypertension or HIV infection) [38]. In addition, the significantly poor survival for Hb SC patients with pulmonary hypertension highlights the need for including this important subgroup of SCD patients in therapeutic clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adults with SS-associated pulmonary hypertension may have hypoxemia secondary to sickle cell-induced pulmonary vascular and parenchymal injury, which is also true for our patient. 6 A more recently appreciated factor predisposing to SS-associated pulmonary hypertension in adults with SS is hemolysis. Intravascular hemolysis leads to elevated plasma-free hemoglobin and release of erythrocyte arginase with secondarily impaired nitric oxide availability.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hemolysis causes an increase in cell-free Hb, which leads to increased consumption and resistance to the activity of Nitric Oxide (NO), which subsequently leads to poor vasodilation [25]. In addition, regional hypoxia from pulmonary infection, fat embolism, and undetected vaso occlusion can lead to chronic fibrotic pulmonary changes and vascular remodeling [26]. Approximately 40% of SCD patients with PH will have features of pre capillary PH, while 50-60% will have some degree study found a similar increase in PPV of TRV ≥ 2.5 m/s when combined with either an NT-pro-BNP level greater than 164 pg/ml or a 6-minute walk distance less than 333 m. Age at screening may play a factor.…”
Section: Pulmonary Hypertension Epidemiology and Diagnosismentioning
confidence: 99%